AB0642 Are Anti-Srp Autoantibodies Specific for Myositis?. (10th June 2014) - Rodríguez-Muguruza, S.; Lozano-Ramos, I.; Hernández-Gallego, A.; Ojanguren, I.; Riveros-Frutos, A.; Holgado, S.; Mateo, L.; Tena, X.; Coll Canti, J.; Martínez-Cácerez, E.; Olive, A.
Abstract : Background: Myositis-specific auto-antibodies (Ab) include those directed against aminoacyl-tRNA synthetases (ARS), signal recognition particle (SRP) and nuclear helicase Mi-2. Anti-SRP Ab is one of the most abundant and best characterized Ab anti-RNP particles. They are mainly associated with aggressive disease, poor prognosis and resistance to steroid therapy. Objectives: To determine the clinical features, serologic features and long-term prognosis among patients with the anti-SRP Ab. Methods: Design: retrospective (2000–2013). Hospital: academic tertiary hospital. Referral area: 850.000 inhabitants. We reviewed the medical records of patients with polymyositis (PM) or dermatomyositis according to the criteria of Bohan and Peter, patients with a condition suggesting the clinical diagnosis of PM and patients with anti-cytoplasmic Ab, regardless of diagnosis. We selected patients with anti-SRP positive and we report the clinical and laboratory features. The past and current status was assessed from hospital records, through a posterior questionnaire, personal interview and electromyography (EMG) test was performed. Anti-nuclear Ab, anti-tissue Ab (AMA, LC, LKM) were tested at diagnosis by indirect immunofluorescence on Hep-2000 cells (Immunoconcepts®) and home-made tissue respectively. Myositis-specific Ab: anti-ARS (Jo-1, PL7, PL12) and anti-SRP were tested by immunoblot (Orgentec®). In addition, levels of creatin-quinase (CK) were measured by turbidimetry (Roche®) Results: Eight patients were positive for anti-SRP Ab, (6 Caucasians and 2 north-african women; mean age 63 years). Three of them (37.5%) had PM (1 associated to systemic sclerosis). At initial evaluation muscle weakness was severe in 2 patients (defined as <3 of manual muscle strength testing) associated to dysphagia and respiratory muscle involvement. The season of onset of muscle weakness was: 2 in the spring and 1 in winter. All 3 patients were treated with glucocorticoids; 2 required immunosupressive agents (methotrexate, azathioprine, rituximab or intravenous immunoglobulin). The histologic study of biceps brachii muscle was performed during the initial diagnostic evaluation and before treatment. It showed histological changes consistent with necrotising myopathy with scarce inflammatory cells. All the other patients (62.5%) had no features of myositis after a follow-up of 6 months to 3½ years. Furthermore most of them (4/5) had a normal EMG and their levels of CK were normal. Their diagnoses were: rheumatoid arthritis, Sjögren's syndrome, autoimmune hepatitis, primary biliary cirrhosis (pure and associated to systemic sclerosis). There were no deaths or history of malignancy among the 8 anti-SRP patients. Conclusions: Although anti-SRP remains as specific Ab for PM, it is occasionally detected in patients with other rheumatic diseases and autoimmune hepatitis in the absence of myositis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3621